Margem de contribuição e a programação linear na atividade agrícola: o caso de uma empresa produtora de sojas especiais - Paula, Wanderson Luiz de (2008)
The present study has as main objective to verify as optimizing the contribution margin in the companies producing of special soy using the lineal programming. Being taken into account that in the agricultural activity, the concept of contribution margin assumes an extremely volatile behavior, in function of the existent dependence between the consumption of resources and several production factors such an as: the climate, the soil, the technology, etc.. it was Looked for to verify the behavior of the contribution margin due to the several factors and to find a form of optimizing the economical result (I profit) through the job of techniques of operational research especially the lineal programming. For so much an empiric research was accomplished in a company producing of special soy. Verified that cannot be had as with base to find the variable costs the produced amount to calculate the contribution margin. The one that she identified was that the variable costs should be had as reference the area planted following production patterns, quality and productivity. Developed these concepts the optimization of the result (I profit) it was been through the facilitated lineal programming, however in the present study he/she worked her with discreet data, being fit for future studies the use of statistical data.